Improving awareness and management of polycystic ovary syndrome - Wiwik Kusumawati; Supriyatiningsih Wenang; Alfaina Wahyuni (Science Midwifery, 2025)
The most common infertility causes among couples at AMC are oligoasthenoteratozoospermia in males (40%) and polycystic ovary syndrome (PCOS) in females (40%). This study aimed to develop an interprofessional collaboration model for the management of PCOS at the Reproductive and IVF Clinic of AMC Muhammadiyah Hospital, with the goal of improving patients’ medication adherence and therapy effectiveness. As the initial phase, a PCOS health education webinar was conducted to enhance participants’ knowledge and attitudes toward PCOS prevention and management. A pre- and post-test design was employed using an online questionnaire distributed via Google Forms to PCOS community members in Yogyakarta. The instrument assessed participants’ knowledge of PCOS, medication adherence, and perceptions of interprofessional collaborative management. Data was analyzed using SPSS software. Thirty-one women participated, of whom 14 (36%) had PCOS, with a median age of 27 years (range: 18–62). The educational webinar significantly improved participants’ understanding of PCOS (p < 0.000), particularly in terms of knowledge and attitudes regarding its prevention and management. The health education webinar effectively enhanced participants’ knowledge and attitudes toward PCOS prevention and management, highlighting the potential of interprofessional collaboration–based education to support comprehensive reproductive health care.